The hesitancy in the nutritional prevention - Alonzo, E.; Bonaccorsi, G.; Cairella, G.; Carreri, V.; Guberti, E.; Nucci, D.; Panunzio, M. F.; Valerio, E. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Our letter discusses the concept of ‘Nutritional Prevention Hesitancy’, comparing it to the well-studied phenomenon of ‘Vaccine Hesitancy’. Both hesitancies can be fueled by ‘infodemics’, the rapid spread of accurate and inaccurate information that can lead to public confusion and mistrust in authoritative sources. Drawing parallels between the two, the text highlights that nutritional prevention hesitancy can result in individuals not adopting evidence-based nutritional strategies, potentially leading to poorer health outcomes. The text emphasizes the critical role of diet in preventing diseases such as heart disease, diabetes, and certain types of cancer, and underscores the need for multifaceted strategies to combat misinformation and promote healthier dietary habits.